A species-diagnostic SNP panel for discriminating lodgepole pine, jack pine, and their interspecific hybrids ... - Dang, S.; Cullingham, Catherine I.; Cooke, Janice E. K.; Coltman, David W. (University of Alberta Library, 2013)
Accurate stock identification is important for forest management, yet this can be a challenge for tree species that hybridize naturally. Species discriminating molecular markers provide a means to identify stock with high accuracy. In Canada, lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia) and jack pine (P. banksiana Lamb) form a large hybrid zone in Alberta and Northwest Territories; within this hybrid zone, the identification of parentals and hybrids is difficult due to an overlap in morphological characteristics. Pure and hybrid ancestry can be resolved using microsatellite markers, but these are difficult and costly to type. We have developed a panel of SNP markers using 454 transcriptome sequence data that are more cost effective, easier to score and have greater discriminating power for differentiating species than microsatellites. Our SNP panel provides accurate and cost efficient forest seed stock identification and will thereby facilitate reforestation and our pipeline can be applied ...